Oral health knowledge of elementary students - Yvatrani, Indah Dewi; Setiawan, Asty Samiaty; Sutardjo, Dede (Faculty of Dentistry Universitas Padjadjaran, 2015)
Introduction: Dental treatment is considered not very important, but the benefits are vital in supporting health and appearance. Oral health knowledge affects a person’s behavior of maintaining oral hygiene. Efforts to oral health care should be done at early age. The purpose of this study was to determine oral health knowledge of students in grade 5 and 6 of Sekeloa 1 and 2 Elementary School Bandung. Methods: This study was a descriptive study with survey method. The method used in sampling was total sampling with a sample size of 158 students in grade 5 and 6 in Sekeloa 1 and 2 Elementary School Bandung. The data was obtained by distributing questionnaires to the objects. Results: Oral health knowledge of student’s in grade 5 and 6 in Sekeloa 1 and 2 Elemantary School Bandung are in 38 respondents (24.1%) with good category; 85 respondents (53,8%) with moderate category; and 35 respondents (22.2%) with less category. Conclusion: Oral health knowledge of 5 and 6 grades of Sekeloa 1 and 2 Elementary School Bandung was moderate.